Comment on: Differential effect of anticoagulation according to cognitive function and frailty in older patients with atrial fibrillation. Issue 4 (11th January 2023) - Kudo, Masataka; Ito, Hideyuki; Sato, Kotaro; Nagayama, Hirofumi; Fujisawa, Satoshi; Yoshioka, Takashi
Abstract : See the Reply by Weijia Wang .